Diverticular Disease Worsening Is Associated with Increased Oxidative Stress and Gut Permeability: New Insights by Circulating Biomarkers - Lucia Pallotta; Vittoria Cammisotto; Valentina Castellani; Alessia Gioia; Margherita Spigaroli; Dominga Carlomagno; Simona Bartimoccia; Cristina Nocella; Martina Cappelletti; Stefano Pontone; Roberto Carnevale; Francesco Violi; et al. (MDPI AG, 2023)
Diverticular disease (DD) management is impaired by its pathogenesis, which is still not completely defined, with an unmet clinical need for improved therapies. Ex vivo DD human models demonstrated the presence of a transmural oxidative imbalance that supports an ischemic pathogenesis. This study aimed to assess, with the use of circulating biomarkers, insights into DD pathogenesis and possible therapeutic targets. Nox2-derived peptide, H2O2, antioxidant capacity, isoprostanes, thromboxanes, TNF-α, LPS and zonulin were evaluated by ELISA in healthy subjects (HS) and asymptomatic and symptomatic DD patients. Compared to HS, DD patients presented low antioxidant capacity and increase in sNox2-dp, H2O2 and isoprostanes paralleled to a TNFα increase, lower than that of oxidative markers. TxB2 production correlated to Nox2 and isoprostanes, suggesting platelet activation. An increase in zonulin and LPS highlighted the role of gut permeability and LPS translocation in DD pathogenesis. The increase of all the markers statistically correlated with DD severity. The present study confirmed the presence of a main oxidative imbalance in DD and provides evidence of platelet activation driven by LPS translocation. The use of circulating biomarkers could represent a new clinical tool for monitoring disease progression and validate therapeutic strategies never tested in DD as antioxidant supplementation.